Effect of supplemental fat and thermal stress on nitrogen and energy metabolism of finishing heifers - Brandt, Robert T., Jr.; Williams, J.E.; Jones, Timothy J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Twelve British and British crossed heifers fed whole shelled corn finishing diets were used in a 2 × 2 factorially arranged experiment to study the main effects of and interactions between feeding supplemental tallow (0 vs 4%) and thermal heat stress (55°F vs 90°F). Heifers were maintained in temperature- and humidity-controlled environmental rooms. Neither supplemental fat or thermal stress affected dry matter intake or total tract digestibility of organic matter, starch, NDF, or ADF. However, heat stress elevated water consumption (P<.01) and rectal temperature (P<.01). When fed at equal intakes, heifers consuming tallow-supplemented diets retained more (P<.05) nitrogen, and tallowsupplemented diets had a higher (P=.08) ME value than non-tallow diets; these effects were not observed when heifers were fed ad libitum. Adding tallow to diets of finishing cattle may help maintain performance under circumstances where feed intake is restricted.
Keywords: Beef; Beef heifers; Metabolism; Tallow; Thermal stress